1997
DOI: 10.1037/1076-898x.3.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Situation awareness during driving: Explicit and implicit knowledge in dynamic spatial memory.

Abstract: This study investigated people's ability to monitor changing spatial information in a simulated driving task. Drivers' knowledge of the locations of traffic cars was assessed with both direct recall measures and indirect performance measures. The direct and indirect measures were positively correlated (associated), suggesting that drivers' knowledge of nearby cars is largely explicit with little contribution of implicit knowledge. When there were too many traffic cars to monitor, drivers used cues such as car … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
121
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(127 citation statements)
references
References 38 publications
4
121
0
2
Order By: Relevance
“…Thus, under some circumstances, efference copies of motor commands elicited during self-initiated movement may be less critical to spatial updating than other sources, such as vestibular and proprioceptive information. These findings are consistent with some spatial cognition studies (Wang & Simons, 1999;Yardley & Higgins, 1998), but not others (e.g., Gugerty, 1997;Larish & Andersen, 1995;Péruch et al, 1995). One possible explanation for this discrepancy is the complexity of the self-movement tested.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Thus, under some circumstances, efference copies of motor commands elicited during self-initiated movement may be less critical to spatial updating than other sources, such as vestibular and proprioceptive information. These findings are consistent with some spatial cognition studies (Wang & Simons, 1999;Yardley & Higgins, 1998), but not others (e.g., Gugerty, 1997;Larish & Andersen, 1995;Péruch et al, 1995). One possible explanation for this discrepancy is the complexity of the self-movement tested.…”
Section: Discussionsupporting
confidence: 81%
“…For example, active participants are better than passively moved participants at predicting future self-positions within simulated optic flow fields (Larish & Andersen, 1995). Active navigation through a simulated driving scene also has been shown to elicit greater recall of the locations of potentially dangerous cars than passive navigation (Gugerty, 1997). However, other studies suggest that active control may be less critical to spatial processing.…”
Section: Going Beyond the Retinamentioning
confidence: 86%
See 1 more Smart Citation
“…This could explain why, in our results, men continue to focus on moving vehicles before and during crossing, whereas traffic lights are only looked at before crossing. Though Endsley's model was first built to account for situation awareness in aeronautics, it has been applied to different domains such as driving (Gugerty, 1997), internet shopping (Lee et al, 2003) and emergency medical dispatch (Blandford and Wong, 2004). Thus, we believe this concept can also be transferred to road crossing tasks, especially in complex situations such as those studied here for crossroad crossing, where pedestrians cope with multiple sources of information coming from the different sides of the crossroads.…”
Section: Discussionmentioning
confidence: 99%
“…Collier and Folleso (1995) also reported good reliability for SAGAT when measuring nuclear power plant operator SA. Also, in a driving task study (Gugerty, 1997) reported good reliability for the percentage of cars recalled, recall error and composite recall error. Regarding validity, Endsley et al (2000) reported a good level of sensitivity for SAGAT, but not for real time probes (on-line queries with no freeze) and subjective SA measures.…”
Section: Freeze Probe Techniquesmentioning
confidence: 99%